Combining multiband slice selection with consistent k‐t‐space EPSI for accelerated spectral imaging. Issue 3 (16th April 2019) - Schmidt, Rita; Seginer, Amir; Tal, Assaf
Abstract : Purpose: To design and implement a multislice MRSI method for fast spectroscopic imaging, using a modified version of echo planar spectroscopic imaging (EPSI) that offers higher spectral width and/or shorter scan time. Methods: Echo planar spectroscopic imaging suffers from inconsistencies between readout lines acquired with gradients of opposite signs, which has typically been addressed by reconstructing the "positive" and "negative" data sets separately and averaging the two. Nevertheless, consistency between the readout lines of each phase encode can be achieved by interposing the EPSI readouts with alternating "blipped" phase‐encode gradients. This method exchanges inconsistencies along the temporal dimension with inconsistencies along the phase‐encode dimension, which are straightforward to correct, as is conventionally done in various EPI reconstruction schemes. Such consistent k‐t‐space EPSI doubles the spectral width in comparison to EPSI, or, in an alternative realization, yields the same spectral width as EPSI, but at half the acquisition time. In this work, multiband CAIPIRINHA (controlled aliasing in parallel imaging results in higher acceleration) slice selection was integrated with consistent k‐t‐space EPSI to further accelerate the measurement 2‐fold. Results: The feasibility of a consistent k‐t‐space EPSI was demonstrated in both phantoms and in vivo brain imaging at 3 T, and four pulse scheme variants were evaluated. It was demonstrated to be useful in optimizing the spectral width and scan acceleration, both of which are limiting factors in vivo. Dual‐band implementation was shown to shorten the duration of the scan 4‐fold. Conclusion: The consistent k‐t‐space EPSI can be used to accelerate MRSI or, alternatively, double its spectral width. Adding dual‐band CAIPIRINHA further accelerates the acquisition by a factor of 2.